PENERAPAN MEDIA VIDEO ANIMASI MELALUI BIMBINGAN KELOMPOK UNTUK MENINGKATKAN MINAT BELAJAR SISWA DI SMP N 1 BAITUSSALAM - Rahayu Ulandari; Wanty Khaira (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effectiveness of implementing animated video media through group guidance services in increasing students' interest in learning at SMP Negeri 1 Baitussalam. The type of research used is quantitative research with an experimental method using the One Group Pre-test Post-test design. The research subjects consisted of 8 students who had low levels of interest in learning based on the pre-test results. The instrument used was a learning interest questionnaire with 37 statement items that had been declared valid and reliable. Data analysis techniques included descriptive analysis, normality test, paired sample t-test, and N-Gain test. The results showed that there was an increase in students' interest in learning after being given the treatment, as indicated by an increase in the average score from 96.50 on the pre-test to 112.88 on the post-test. The t-test results showed a significance value of 0.000 (< 0.05), which means there is a significant difference between before and after the treatment. Furthermore, the N-Gain test results obtained an average value of 0.3182, which falls into the medium category. Thus, it can be concluded that the implementation of animated video media through group guidance is effective in increasing students' interest in learning.